Language Learning Styles and Strategies Among Malaysian Students - Ahamad Shah, Mohamed Ismail; Ismail, Yusof; Esa, Zaleha; Muhamad, Ainon Jariah (2010)
This study investigated the relationship between learning styles and learning strategies of Malaysian students studying English through Content-based Instruction (i.e. English for Academic Purposes and English for Occupational Purposes) at the International Islamic University Malaysia (IIUM). Learning styles and learning strategies of language learners play important roles in second language acquisition. The learning styles were investigated through an analysis of their responses to Learning Styles Indicator (LSI) (2003) while learning strategies were investigated through Rebecca Oxford’s Strategy Inventory for Language Learning (SILL) (1990). The study was mainly motivated by concerns about the standards of English among graduates who have been observed to be passive and reticent in the language classrooms compared to international students. An understanding of learning styles and strategies of students will enable language educators to adjust their instructional styles and strategies and provide the most appropriate instruction to the students. Preliminary results seem to suggest certain learning strategies contribute statistically significantly toward learning styles. The study will draw implications from the study for language teaching in terms of how teachers need to adjust their own instructional styles and strategies to suit those of the students.